An efficient one-pot synthesis of 2-aminothiazoles via electrochemically oxidative α-C-H functionalization of ketones with thioureas. Issue 3 (June 2022) - Li, Pei; Yang, Shang-Feng; Fang, Zi-Lin; Cui, Hao-Ran; Liang, Sen; Tian, Hong-Yu; Sun, Bao-Guo; Zeng, Cheng-Chu
Abstract: An efficient one-pot electrochemical protocol for the synthesis of 2-aminothiazoles has been described from electrolysis of ketones with thioureas mediated by iodide ion. The electrochemical synthesis was conducted in an undivided cell equipped with graphite plates electrodes under constant current conditions. A diversity of aromatic and aliphatic ketones was suitable for the reaction, yielding the corresponding 2-aminothiazoles in satisfactory yields. Mechanistically, the in-situ generated α-iodoketone was proposed to be a key active species. Graphical Abstract: ga1 Highlights: An efficient one pot electrochemical synthesis of 2-aminothiazoles from ketones and thioureas mediated by iodide is described. The environmentally benign approach proceeds in an undivided cell without additional oxidants and metal catalysts. Mechanistically, the in-situ generated α-iodoketones was proposed to be the key active species. The method can be readily carried out in gram-scale and successfully applied to the synthesis of Fanetizole.